2020
DOI: 10.1007/s10236-020-01397-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of river plumes in the South Brazilian Bight and South Brazil

Abstract: The plumes from the rivers of the South Brazilian Bight (SBB) and South Brazil (SB) were studied using a realistic model configuration. River plume variability on continental shelves is driven by the input of river runoff into the shelf, by wind variability, and also by ambient currents and its seasonal variability, especially the Brazil Current, which are realistically modelled in this study. It is presented a simulation of 4 years using a nested configuration, which allows resolving the region around Florian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
0
18
0
1
Order By: Relevance
“…In the South Brazilian Bight and South Brazil, a permanent continuous Brazil Current flows southward along the slope. By releasing passive dyes together with the river discharge in the hydrodynamical model, Marta-Almeida et al (2021) showed that the local river plumes are confined to the inner shelf because the strong and persistent large-scale Brazil Current flowing southward over the slope prevents the river plumes from interaction with offshore oceanic mesoscale dynamics. The effect of mesoscale eddies on river plumes was conducted in the Agulhas Mozambique Channel region (Malauene et al, 2018), where the circulation is dominated by trains of intermittent, passing mesoscale eddies.…”
Section: Role Of Mesoscale Circulation On River Plumesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the South Brazilian Bight and South Brazil, a permanent continuous Brazil Current flows southward along the slope. By releasing passive dyes together with the river discharge in the hydrodynamical model, Marta-Almeida et al (2021) showed that the local river plumes are confined to the inner shelf because the strong and persistent large-scale Brazil Current flowing southward over the slope prevents the river plumes from interaction with offshore oceanic mesoscale dynamics. The effect of mesoscale eddies on river plumes was conducted in the Agulhas Mozambique Channel region (Malauene et al, 2018), where the circulation is dominated by trains of intermittent, passing mesoscale eddies.…”
Section: Role Of Mesoscale Circulation On River Plumesmentioning
confidence: 99%
“…Previous studies have used numerical models to trace the riverine freshwater by releasing dyes into the rivers in many coastal regions, such as the New York Bight (Zhang et al, 2010), the Rhine Region (Rijnsburger et al, 2021), the South Brazilian Bight (Marta-Almeida et al, 2021), the Yangtze River estuary (Yu et al, 2020;Wu et al, 2021), and the Great Barrier Reef (Colberg et al, 2020). Three-dimensional structure and evolution of the river plumes have been presented in these numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…For each baroclinic timestep, 30 s barotropic timestep was defined. ROMS was successfully applied in previous studies focused on Madeira Island to investigate island-induced oceanic processes (Caldeira and Sangrà, 2012;Couvelard et al, 2012;Caldeira et al, 2016;Alves et al, 2021) and has also been used in idealized and realistic studies to investigate plume dynamics generated by the Columbia, Pearl, and South Brazilian rivers (Chen et al, 2009;Liu et al, 2009;Pan et al, 2014;Basdurak et al, 2020;Branch et al, 2020;Marta-Almeida et al, 2020). Despite the lack of in situ data to assess the accuracy of the coupled ROMS model outputs during February 2010, Vieira et al (in preparation) are (at the time of publication) assessing the general capability of our numerical framework to represent island-scale geophysical processes, including warm wakes, storm events, and land runoff.…”
Section: Oceanic Modelmentioning
confidence: 99%
“…Such torrential discharge often generates buoyant river plumes that are easily identified by the high levels of suspended matter that spread from river mouths and mix with the surrounding oceanic waters. According to Osadchiev and Zavialov (2020), the formation, mixing, and spreading of buoyant river plumes depends on several factors that may be divided into two groups: (i) site characteristics, such as the geometry of the coastline and river mouths, bathymetry, and latitudedependent Coriolis force (Chao and Boicourt, 1986;Simpson, 1997;Garvine, 1999;Horner-Devine et al, 2006, 2015McCabe et al, 2009;Warrick and Farnsworth, 2017); and (ii) external forcing mechanisms, such as river flow, wind, coastal currents, tides, waves, and water column stratification Geyer, 2001, 2002;Yankovsky et al, 2001;Wu et al, 2011;Korotenko et al, 2014;Osadchiev, 2018;Yuan et al, 2018;Zhao et al, 2018;Marta-Almeida et al, 2020). Thus, the land-sea discharges of freshwater, terrigenous sediments, nutrients, suspended matter, and anthropogenic contaminants or pollutants affect the physical, chemical, biological, and geological processes in the coastal environment (Milliman and Syvitski, 1992;Meybeck et al, 2003;Brodie et al, 2010;Hilton et al, 2011;Bao et al, 2015;Warrick and Farnsworth, 2017;Osadchiev, 2018;Osadchiev and Zavialov, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Marta-Almeida et al ( 2021 ) used a very high-resolution nested configuration of the Regional Ocean Modeling System (ROMS) to study the dynamics of river plumes in the South Brazilian Bight and the influence of the Brazil Current (BC). Results show that the BC prevents the river plumes from interaction with oceanic mesoscale features, so that river plumes are mainly controlled by wind forcing.…”
Section: Four Papers Focused On Tides River Flows and Coastal Sea Lmentioning
confidence: 99%